2011
DOI: 10.3368/le.87.3.508
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and Production Cost Impacts of No-till in Finland: Estimates from Observed Behavior

Abstract: No-till has been promoted as a cultivation method that reduces both production costs and the environmental impacts of farming relative to conventional tillage. Using farmlevel data from Finland, we show that no-till has no statistically significant effect on total variable costs but that it increases the use of plant protection products and fertilizers, and decreases the use of labor. An environmental impact simulation combining the results on input use with a nutrient and herbicide runoff model predicts that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…Our findings suggest that adopters have responded by increasing herbicide use . Similarly, Laukkanen and Nauges () found that CT adoption increases both chemical fertiliser and herbicide use. On the other hand, Teklewold et al .…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…Our findings suggest that adopters have responded by increasing herbicide use . Similarly, Laukkanen and Nauges () found that CT adoption increases both chemical fertiliser and herbicide use. On the other hand, Teklewold et al .…”
Section: Resultsmentioning
confidence: 90%
“…It can sequester carbon and contribute to climate mitigation according to Lal () and others. However, there are also concerns that it could be accompanied by increased use of herbicides to mitigate potential weed incidence, which could adversely affect the environment (Laukkanen and Nauges ) and health (Sheahana et al . ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(, ), Groom et al . () and Laukkanen and Nauges (). This assumption should not influence our conclusions.…”
mentioning
confidence: 98%
“…We focus on revenue as a measure of farmer's welfare. We assume that climate is the primary source of production risk, thus modelling farmers as price-takers and assuming that prices are perfectly predictable in the short-run, see alsoKoundouri et al (2003Koundouri et al ( , 2006,Groom et al (2008) andLaukkanen and Nauges (2011). This assumption should not influence our conclusions.…”
mentioning
confidence: 99%